Policies to establish and open access digital resources in some advanced countries - Thua, Nguyen Thi; Xa, Luu Xuan; Thuy Quynh, Dinh Thi; Kiem, Cao Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Scientific research is increasingly focused on in order to boost the economy in many countries. It is imperative to have the most up-to-date scientific works to meet the needs of national development, to share scientific research data around the world. However, each country, depending on their management mechanism, has different policies for the establishment of digital resources and open access to these types of documents. From the fact, the article will presents the policies of developing digital resources and open access in G7 countries - the group of power countries in the world, to better understand the situation of resources development and the way to effectively exploit this resource. Since then, the article will draw on some reference experiences for open access to research data in Vietnam. Code: 16122901